Non‐phthalate plasticizer DEHT preserves adequate blood component quality during storage in PVC blood bags. Issue 1 (12th September 2020) - Larsson, Linda; Sandgren, Per; Ohlsson, Sara; Derving, Julia; Friis‐Christensen, Tove; Daggert, Felicia; Frizi, Naïma; Reichenberg, Stefan; Chatellier, Sonia; Diedrich, Beatrice; Antovic, Jovan; Larsson, Stella; et al.
Abstract : Background and objectives: Commercial blood bags are predominantly made of polyvinyl chloride (PVC) plasticized with di(2‐ethylhexyl) phthalate (DEHP). DEHP is favourable for storage of red blood cells (RBC). Historically, removal of DEHP from blood bags has been linked to unacceptable haemolysis levels. Oncoming regulatory restrictions for DEHP due to toxicity concerns increase the urgency to replace DEHP without compromising RBC quality. Di(2‐ethylhexyl) terephthalate (DEHT) is one suggested substitute. The aim of this study was to compare PVC‐DEHT to PVC‐DEHP blood bags using additive solutions saline–adenine–glucose–mannitol (SAGM) and phosphate–adenine–glucose–guanosine–saline–mannitol (PAGGSM), to determine whether DEHT can maintain acceptable component quality. Materials and methods: RBC concentrates (N = 64), platelet concentrates (N = 16) and fresh frozen plasma (N = 32) were produced from whole blood collected into either DEHT or DEHP plasticized systems. Using a pool‐and‐split study design, pairs of identical RBC content were created within each plasticizer arm and assigned either SAGM or PAGGSM. Storage effects were assessed weekly for 49 days (RBC), 7 days (platelets) and before/after freezing (plasma). Results: Though haemolysis was slightly higher in DEHT, all study arms remained below half of the European limit 0·8%. K + was lower in DEHT than in DEHP independent of additive solution. The metabolic parameters were not influenced by choice of plasticizer. Platelet activation/metabolism and plasma content were similarly preserved. Conclusion: Our study demonstrates that the plasticizer DEHT provides adequate blood component quality. We propose DEHT as a strong future candidate for replacement of DEHP in blood bags.